Діяльність дипломатичної місії УНР на Паризькій мирній конференції (липень-грудень 1919 р.) (Zaporizhzhia Historical Review, 2021)
This article is about the activity of delegation People’s Republic of Ukraine on conference of peace in Paris on July-December, 1919. This period, in author opinion, practicaly was a determinant fact Peopl’es Republic of Ukraine on international politics scene. In this work analize not only the diplomatic talks between ukrainian diplomatist and sporesman of members of Entente, but also definity a basic reason of political split in common deligation Peopl’es Republic of Ukraine.